Nodular fasciitis adjacent to the left humerus in a 15-year-old boy - Keita Sasa; Yoshiyuki Suehara; Tatsuya Takagi; Kei Sano; Takuo Hayashi; Tsuyoshi Saito (Elsevier, 2021)
Nodular fasciitis is often misdiagnosed as its histological mimics, including malignant tumors, due to high levels of cellularity and the presence of occasional mitotic figures. A 15-year-old boy noticed a mass on his left shoulder and was admitted to the hospital. Based on magnetic resonance imaging (MRI) results, the lesion seemed to be located within the muscle, just below the subcutaneous adipose tissue and adjacent to the periosteum of the left humerus. It showed an iso-low signal on T1-weighted images, a heterogeneously high signal on T2-weighted images, and a hyperintense signal on T2 fat-suppression. A fascial tail sign was observed in T2 and T2 fat-suppression sagittal slices. Although the lesion was diagnosed as nodular fasciitis by biopsy, the lesion gradually increased in size up to 3.7 cm during 2 months of follow up after the first admission. The lesion was surgically resected with the marginal margin. Histological analysis showed fascicular proliferation of spindle-shaped cells with inflammatory infiltrates and stromal bleeding. A diagnosis of nodular fasciitis was confirmed by the detection of an MYH-USP6 fusion transcript. The identification of this fusion gene helped to avoid an unnecessary surgical procedure. The patient has been followed up for 6 months after surgery without any evidence of recurrence.